The Reductive Activity of Human Liver Microsomes for Vitamin K Epoxides - Masashi Kawano; Takuya Araki; Hideaki Yashima; Tomonori Nakamura; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2020)
Vitamin K (VK) is oxidized to vitamin K epoxide (VK-O) during the production of VK-dependent blood clotting factors. Thereafter, VK-O is reduced to VK by vitamin K epoxide reductase (VKOR) in the liver and reused. This reductive reaction is inhibited by warfarin, an oral anticoagulant. VK in nature is roughly divided into two types, VK1 (phylloquinone) and VK2 (menaquinone). Although their bioavailabilities and elimination half-lives from human blood differ, information on the influence of each VK on the effectiveness of warfarin is limited. In this study, the difference in the metabolism of VK1-O and MK4-O by VKOR was evaluated in an in vitro study using human liver microsomes. The results showed that the substrate affinity (1/Km), and the maximum reaction rate (Vmax) of the VKOR reduction was around 7 and 4 times higher for MK4-O than for VK1-O, respectively. The intrinsic clearance of MK4-O, obtained by dividing the Vmax value by the Km value, was about 30 times greater than that of VK1-O. According to these data, the production of VK-dependent blood coagulation factors can be considered to be dominated mainly by MK4-O, at least under normal conditions. We may thus have to be more careful about controlling the intake of MK4 than VK1 in patients receiving warfarin therapy.Keywords: vitamin K1 (phylloquinone), vitamin K2 (menaquinone), VKOR, warfarin